2013
DOI: 10.1371/journal.pone.0071199
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Metabolomic Approach to Identify Uremic Solutes in Plasma of Stage 3–4 Chronic Kidney Disease Patients

Abstract: BackgroundChronic kidney disease (CKD) is characterized by the progressive accumulation of various potential toxic solutes. Furthermore, uremic plasma is a complex mixture hampering accurate determination of uremic toxin levels and the identification of novel uremic solutes.MethodsIn this study, we applied 1H-nuclear magnetic resonance (NMR) spectroscopy, following three distinct deproteinization strategies, to determine differences in the plasma metabolic status of stage 3–4 CKD patients and healthy controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 41 publications
4
40
0
1
Order By: Relevance
“…Using metabolite profiling of plasma samples from 1,434 Framingham study participants, Rhee et al demonstrated that progression to CKD could be predicted using just 9 metabolites (100). Another metabolomic study applied NMR spectroscopy to determine differences in the plasma metabolic status of stage 3–4 CKD patients and healthy controls (101). This study revealed the elevation of 14 metabolites in the plasma of uremic patients, which included several previously identified uremic toxins, such as PCS, as well as two novel uremic retentions solutes, dimethyl sulphone and 2-hydroxyisobutyric acid (101).…”
Section: Gut Microbiome In Ckd Related Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using metabolite profiling of plasma samples from 1,434 Framingham study participants, Rhee et al demonstrated that progression to CKD could be predicted using just 9 metabolites (100). Another metabolomic study applied NMR spectroscopy to determine differences in the plasma metabolic status of stage 3–4 CKD patients and healthy controls (101). This study revealed the elevation of 14 metabolites in the plasma of uremic patients, which included several previously identified uremic toxins, such as PCS, as well as two novel uremic retentions solutes, dimethyl sulphone and 2-hydroxyisobutyric acid (101).…”
Section: Gut Microbiome In Ckd Related Complicationsmentioning
confidence: 99%
“…Another metabolomic study applied NMR spectroscopy to determine differences in the plasma metabolic status of stage 3–4 CKD patients and healthy controls (101). This study revealed the elevation of 14 metabolites in the plasma of uremic patients, which included several previously identified uremic toxins, such as PCS, as well as two novel uremic retentions solutes, dimethyl sulphone and 2-hydroxyisobutyric acid (101). Ideally, to study uremic toxins, both proteomics and metabolomics approaches should be applied as these methods complement each other and each has a unique role in the discovery of uremic retention solutes.…”
Section: Gut Microbiome In Ckd Related Complicationsmentioning
confidence: 99%
“…Metabolomic surveys of earlier stages of CKD have provided insight on how metabolite alterations vary across levels of kidney function [16-19]. Duranton et al used a commercial LC-MS metabolomics vendor to measure amino acids and amino acid derivatives in plasma and urine from 52 individuals across different stages of CKD and plasma only from 25 individuals on dialysis [20].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Metabolomics is defined as the comprehensive and quantitative metabolic analysis of large numbers of endogenous, low-molecular-weight metabolites. In the past decade, the widespread utility of this analytical approach to monitoring multiple metabolic perturbations in living systems within pathological processes [13][14][15][16][17][18][19] , including CKD [17] , and the response to such external stimuli as drug treatments [20,21] has been illustrated. Moreover, this method is now being applied to the field of TCM [22][23][24][25][26] , as it could characterize the subtle metabolic interventions induced by TCM in the treatment of diseases and identify the potential implications of TCM.…”
Section: Introductionmentioning
confidence: 99%